ANALISIS PENGARUH CASH POSITION, DEBT TO EQUITY RATIO DAN RETURN ON ASSETS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBEI PERIODE 2013-2015 - Noviarti (Jurnal Manajemen, 2017)
The Purpose this research is to analyze the effect of Cash Position, Debt to Equity Ratio and Return On Assets of the Dividend Payout Ratio on Manufacturing companies listed on the Stock Exchange in the period 2013-2015. Testing the hypothesis in this study using multiple linear regression analysis. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange (BEI) in the year 2013 to 2015 is 133 companies, while the sample is 43 companies with purposive sampling as the sampling technique. The results of this study prove that Cash Position, Debt to Equity Ratio and Return On Assets simultaneously affect the Dividend Payout Ratio, seen from the F test found significant levels of less than 0.05 is 0.000 <0.05. But only partially Debt to Equity Ratio which significantly influence Dividend Payout Ratio, seen from t test that only the Debt to Equity Ratio is smaller than the significance level of 0.05.